(untitled) (Journal of Hama University, 2022)
The aim of this study was to evaluate the management of facial scars by injecting fat graft alone or with platelet-rich plasma, after preparing the area by injecting it with platelet-rich plasma ten days before. The study was conducted on (40) facial scars present in 40 patients selected according to specific clinical criteria. It was divided into two groups that included 20 scars, the first group was treated with the autologous fat graft, the second group also 20 scars were treated with the autologous fat graft with PRP, patients aged between 18 and 38 years, 32 females and 8 males. Ten days before the process, for both groups, the scar site was prepared by PRP. As for the process of preparing the autologous fat graft, it was carried out through the washing process for both groups. The cases were monitored in stages and evaluated after three and six months, through which three variables were monitored ,the satisfaction of the patient and the satisfaction of the observer and the patient’s desire to restore injections, patient satisfaction was well better in a group with plasma, and in terms of the final evaluation of the aesthetic aspect from the observer’s point of view. It was slightly similar after three months, but after six months, the groups became almost equal in both. After six months, patients wanted to re-inject 30% in the group with PRP, while up to 40% in the group without PRP, : Autologous fat graft with PRP is better in managing facial scars than the Autologous fat graft alone, but without statistically significant differences, where the significance level was greater than 0.05 (P>0.05) and with a confidence degree of 95%, we recommend using Autologous fat graft with platelet-rich plasma in the management of facial scars.